Analisis Pelaksanaan Program FMD Rumah Tahanan Negara Kelas IIa Yogyakarta - Nastiti, Prabasiwi Rekyan; Rifani, Denny Nazaria (Jurnal Ilmiah METANSI ”Manajemen dan Akuntansi”, 2025)
This study aims to analyze the implementation of the FMD Program (Physical, Mental, and Discipline Development) as part of capacity building at the Class IIA Yogyakarta Detention Center. The FMD Program is intended to enhance employee discipline, work enthusiasm, and team cohesion. However, the findings reveal unequal participation, a predominance of recreational activities, and a limited impact on improving employee discipline. This research employs a qualitative descriptive method using the Collaborative Governance Regime (CGR) approach, which includes four dimensions: system dynamics, principled engagement, shared motivation, and capacity for joint action. The study's results indicate that the FMD Program has not been fully adaptive to environmental changes, lacks formal and systematic evaluation, and shows weak internalization of discipline values among employees. Although the program is supported by budget and facilities, the absence of regulatory instruments—such as implementation guidelines and technical instructions—has led to a lack of clear and measurable direction in its execution.A reformulation of the FMD concept is necessary to shift its orientation beyond recreation and toward fostering sustainable behavioral change among staff.